Determinants to utilization of emergency obstetric care services among perinatal clients seeking care at Kajiado County Referral Hospital, Kajiado County, Kenya - Ahmed, Khalid; Njoroge, Harrison C. (International Journal Of Community Medicine And Public Health, 2024)
Background: Worldwide, one or more potentially fatal perinatal obstetric complications affect nearly 15% of all pregnant women. There has been little research on the provision of emergency obstetric care (EmOC) services in Kenya. This study aimed to assess the determinants of EmOC services among perinatal clients seeking care at Kajiado County Referral Hospital, Kajiado County, Kenya. Methods: An analytical cross-sectional study design was embraced in this study while both systematic and simple random sampling were used to recruit study respondents for this research. Associations between the utilization of emergency obstetric care services and associated determinants were established using a Chi-square test and binary logistic regression where a p value of 0.05 or lower was considered significant. Results: The utilization of EmOC services from this research was at 74%. Study respondents aged between 18-25 years (OR=9.4, 95% CI=0.04-0.31), being knowledgeable about EmOC services (OR=3, 95% CI=0.13-9.75), and being knowledgeable about obstetric danger signs (OR=6, 95% CI=0.06-0.45), increased the odds of utilizing EmOC services while earning less than 10000 Kshs (OR=4.3, 95% CI=0.45-4.77), reduced the odds of utilizing EmOC services. Conclusions: The utilization of EmOC services from this research was at 74%. Study respondents aged between 18-25 years, being knowledgeable about EMOC services and being knowledgeable about obstetric danger signs increased the odds of utilizing emergency obstetric care services while earning less than 10000 Kshs reduced the odds of utilizing emergency obstetric care services.